Konsep Subyek Hukum Dalam Hukum Islam Dan Hukum Positif - Iqbal, Muhammad; Zulkifli, Zulkifli (IDRIS Darulfunun Institute, 2026)
Indonesia, as a rule of law state that recognizes every person as an actor under the law, means that every person is recognized as a legal subject. The provisions regarding humans as legal subjects are regulated in Islamic law, referred to as mahk?m ?alaih, as mukallaf individuals. The term legal subject then continued to develop beyond individuals, namely legal entities. This paper aims to illustrate the differences and similarities in the concept of legal subjects in Islamic law and positive law. This research is a library study with a qualitative approach to examine the application of the legal subject concept in Islamic law and positive law in Indonesia. The main data source in this research is from written sources directly related to the study. In data analysis, the author uses qualitative analysis by coding data, reducing data, and drawing conclusions. The development of the term